2019
DOI: 10.1038/s41591-018-0321-2
|View full text |Cite
|
Sign up to set email alerts
|

Translation control of the immune checkpoint in cancer and its therapeutic targeting

Abstract: Cancer cells develop mechanisms to escape immunosurveillance, among which modulating the expression of immune suppressive messenger RNAs is most well-documented. However, how this is molecularly achieved remains largely unresolved. Here, we develop an in vivo mouse model of liver cancer to study oncogene cooperation in immunosurveillance. We show that MYC overexpression (MYCTg) synergizes with KRASG12D to induce an aggressive liver tumor leading to metastasis formation and reduced mouse survival compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
190
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(204 citation statements)
references
References 71 publications
14
190
0
Order By: Relevance
“…) and on-target engagement, as shown by the repression of phospho-eIF4E expression in the melanomas (Figure S7D). These data recapitulate our observations in the phospho-eIF4E deficient BRaf CA/+ /Pten lox/lox (eIF4E KI ) mice, and further supports that systemic inhibition of phospho-eIF4E by blocking MNK1/2, has efficacy in modulating both the tumor and TME in pre-clinical cancer models48,[82][83][84][85] . Strikingly, the combination therapy of SEL201 and anti-PD-1 monoclonal antibody significantly reduced primary melanoma growth, local and distant lymph node metastasis, and increased the overall survival of tumor-bearingBRaf CA/+ /Pten lox/lox mice compared to either of the therapies alone, without causing any overt toxicity (Figure 7C-7F and S7C-S7E).Analysis of plasma cytokine and chemokine levels revealed that the robust anti-tumor effect of SEL201 combined with anti-PD-1 therapy was associated with enhanced peripheral anti-tumor immunity, characterized by a decrease in the immunosuppressive cytokine/chemokine signature, including IL-6, CCL2 and CCL5 (Figure 7H).…”
supporting
confidence: 88%
“…) and on-target engagement, as shown by the repression of phospho-eIF4E expression in the melanomas (Figure S7D). These data recapitulate our observations in the phospho-eIF4E deficient BRaf CA/+ /Pten lox/lox (eIF4E KI ) mice, and further supports that systemic inhibition of phospho-eIF4E by blocking MNK1/2, has efficacy in modulating both the tumor and TME in pre-clinical cancer models48,[82][83][84][85] . Strikingly, the combination therapy of SEL201 and anti-PD-1 monoclonal antibody significantly reduced primary melanoma growth, local and distant lymph node metastasis, and increased the overall survival of tumor-bearingBRaf CA/+ /Pten lox/lox mice compared to either of the therapies alone, without causing any overt toxicity (Figure 7C-7F and S7C-S7E).Analysis of plasma cytokine and chemokine levels revealed that the robust anti-tumor effect of SEL201 combined with anti-PD-1 therapy was associated with enhanced peripheral anti-tumor immunity, characterized by a decrease in the immunosuppressive cytokine/chemokine signature, including IL-6, CCL2 and CCL5 (Figure 7H).…”
supporting
confidence: 88%
“…It was shown that interfering with the function of the eIF4F complex resulted in a decreased expression of PDL-1 either after interfering with translation of STAT1 leading to a lower transcription of PDL-1, or via interfering with eIF4E phosphorylation and activity, in melanoma [104] or liver cancer [105]. These studies demonstrate that checkpoint inhibitors can be translationally modulated and that ribosome inhibitors could be relevant for such a role.…”
Section: Ribosome Inhibitors and Immunotherapiesmentioning
confidence: 81%
“…It is possible that in an in vivo TSC2−/− model, eFT508 might inhibit tumor growth, as was seen in an aggressive liver cancer model [26]. In the latter publication, eFT508 was shown to downregulate the translation of PDL-1 mRNA by the tumors in vivo and enhance survival profoundly [28]. Several studies have shown that either anti-PD-1 or anti-PD-L1 antibodies reduce TSC2-deficient tumor growth in vivo and enhance mouse survival [19,29].…”
Section: Discussionmentioning
confidence: 91%